A new mixed‐integer linear formulation for optimal placement of fault indicators in distribution systems. (21st June 2018) - Derakhshandeh, Sayed Yaser; Nikbakht, Mojtaba
Summary: In distribution systems, fault indicators (FIs) are used for fast faulted line‐section location. Locations and the numbers of FIs affect the reliability indices of distribution companies and customers. This study presents a new linear method to find the optimum numbers and locations of FIs in distribution systems. Fault indicator placement of FIs is defined as an optimization problem whose aim is to improve the reliability indices with regard to the costs imposed on the system. The structure of the proposed formulation is mixed‐integer linear programming. The proposed approach finds the optimal locations for FIs in such a way that customers' interruption cost and investment costs for the installation of FIs are minimized. The proposed formulation can be solved by using commercial solvers in a computational effective manner and rapidly converges to the global optimum. To evaluate the effectiveness of the proposed mixed‐integer linear programming optimization formulation, several studies are presented and tested on bus number 4 of the reliability test system.